Projeto Flora Amazônica: eight years of binational botanical expeditions - Prance, Ghillean Tolmie; Nelson, Bruce Walker; Silva, Marlene Freitas da; Daly, Douglas Charles (Acta Amazonica, 1984)
A review of the history and results of the first eight years of fieldwork of Projeto Flora Amazônica is given. This binational plant collecting program, sponsored by the Conselho Nacional de Desenvolvimento Científico e Tecnológico and the National Science Foundation, has mounted 25 expeditions to many parts of Brazilian Amazonia. Expeditions have visited both areas threatened with destruction of the forest and remote areas previously unknown botanically. The results have included the collection of 32,976 members of vascular plants, 16, 482 of cryptogams, as well as quantitative inventory of 18.67 hectares of forest with the collection of 7,294*** numbers of sterile vouncher collections. The non-inventory collections have been made in replicate sets of 10-13 where possible and divided equally between Brazilian and U.S. institutions. To date, 55 botanists from many different institutions and with many different specialities have taken part with 36 different Brazilian botanists. The resulting herbarioum material is just beginning to be worked up and many nem species have been collected as well as many interesting range extensions and extra material of many rare species.